Mittā Suhadā Veditabbā: The Buddha’s Teaching on True Friendship in the Sigālovāda Sutta - Dr. Ajith Wellington, (South Asian Journal of Religion and Philosophy (SAJRP), 2025)
In Buddhist thought, kalyāṇamitta (spiritual friendship) is regarded as essential for awakening, guiding one along the Noble Eightfold Path. However, the Sigālovāda Sutta introduces a less-examined but vital form of friendship in the words, mittā suhadā veditabbā, or friends who are seen as good-hearted. Unlike the spiritually focused kalyāṇamitta, suhadamitta emphasizes emotionally supportive, socially grounded relationships. The Buddha uses the term suhada (good-hearted) rather than kalyāṇa (noble/spiritual), marking a key distinction in the dimensions of friendship. In the Sutta, he reinterprets the ritual of worshiping the six directions as a symbolic framework for maintaining harmony in six core human relationships: parents, teachers, spouse, friends, religious mentors, and workers, stressing mutual duties over rights. The discourse identifies both harmful and beneficial friendships, highlighting traits of loyalty, compassion, and wise counsel. It also promotes ethical living, prudent wealth management, and mutual care. While suhadamitta supports worldly happiness and moral living, kalyāṇamitta leads to spiritual liberation. Together, these friendships embody Buddhism’s dual goal: fostering social harmony and guiding individuals toward Nibbāna.